The Influence of the Make A Match Learning Model on Student Learning Outcomes in Aqidah Akhlak Learning at MI Syamsul Iman NW in Senurus - Laela Patmawati (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to determine the effect of the